Terrorism Industry and Data Coloniality in Southeast Asia - Ilyas, Mohammed (Journal of Contemporary Governance and Public Policy, 2022)
Decolonisation of academia has become a 'vogue' among scholars, students and activists, which has resulted in many publications on decolonisation. Unlike the social sciences, the online world and digital data have not received much attention from decolonial scholars. Digital data colonialism combines historical colonialism's predatory aspect and computer science ability to quantify and commodify online relations. The organisations responsible for digital data colonialism are big tech companies and powerful Western countries' intelligence agencies. Tech companies gather digital data and sell it for profit to big businesses. While, intelligence agencies of powerful Western gather digital data and use it for national interest and securitisation of populations under the banner of fighting terrorism, which reproduces non-Western countries' coloniality. This paper discusses the coloniality of non-Western countries by powerful Western countries through the use of digital data colonialism, which is carried out by their inelegance agencies and Western tech companies.